The evaluation of depressive, anxiety symptoms and sleep disturbance in college students post- pandemic era across UAE: a multicentric survey - Firoz, Fathima; Jaber, Ammar Ali Saleh (Frontiers in Psychiatry, 2024)
The COVID-19 epidemic has had a significant worldwide impact, requiring measures such as quarantine, social isolation, and the closing down of educational institutions, increasing concerns about student safety. This study evaluated the mental health and sleep status of 201 college students in the UAE after the epidemic. The sample consisted primarily of females (72.1%) and students aged 21-23 years (42.3%), with the majority residing in Dubai (62.7%). The findings revealed unsettling levels of insomnia risk and significant gender variations in emotional states, with females displaying higher degrees of distress. These findings underscore the negative consequences of the pandemic on student well-being and the importance of having access to mental health care, as well as calling for specialized treatments to address the individual needs of various student groups.